2007
DOI: 10.1016/j.bbr.2007.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors modulates the induction and expression of amphetamine-induced behavioral sensitization partially through an associated learning of the environment in mice

Abstract: The behavioral sensitization produced by repeated amphetamine treatment may represent the neural adaptations underlying some of the features of psychosis and addiction in humans. Chromatin modification (specifically histone hyperacetylation) was recently recognized as an important regulator of psychostimulant-induced plasticity. We have investigated the effects of treatment with the histone deacetylase (HDAC) inhibitors butyric acid (BA, 630 mg/kg, i.p) and valproic acid (VPA, 175 mg/kg, i.p.) on the psyhcosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 40 publications
5
75
0
Order By: Relevance
“…Conversely, acetylation-related processes seem less relevant in the development of drug tolerance and dependence (as measured by the intensity of drug withdrawal), which result from transient homeostatic adaptations occurring within the cells and circuits directly stimulated by each drug and are not considered core symptoms of addiction (Hyman et al, 2006). This view is in agreement with earlier pharmacological and genetic studies on psychostimulants-induced sensitization and CPP (Bilbao et al, 2008;Kalda et al, 2007;Kumar et al, 2005;Levine et al, 2005;Renthal et al, 2007), as well as with the few preceding studies indicating that HDACis do not facilitate the development of tolerance (Wang et al, 2007) and that histone acetylation might be more involved in the expression than in the induction of drug dependence (Pandey et al, 2008). Future studies should further explore this intriguing dissociation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Conversely, acetylation-related processes seem less relevant in the development of drug tolerance and dependence (as measured by the intensity of drug withdrawal), which result from transient homeostatic adaptations occurring within the cells and circuits directly stimulated by each drug and are not considered core symptoms of addiction (Hyman et al, 2006). This view is in agreement with earlier pharmacological and genetic studies on psychostimulants-induced sensitization and CPP (Bilbao et al, 2008;Kalda et al, 2007;Kumar et al, 2005;Levine et al, 2005;Renthal et al, 2007), as well as with the few preceding studies indicating that HDACis do not facilitate the development of tolerance (Wang et al, 2007) and that histone acetylation might be more involved in the expression than in the induction of drug dependence (Pandey et al, 2008). Future studies should further explore this intriguing dissociation.…”
Section: Discussionsupporting
confidence: 82%
“…Recent studies have provided initial support to this hypothesis. For example, the administration of psychostimulants, such as cocaine, at dosages that promote conditioned place preference (CPP) or locomotor sensitization results in histone hyperacetylation at specific loci relevant to the development of addictive behavior (Kumar et al, 2005;Levine et al, 2005;Renthal et al, 2008aRenthal et al, , 2007 and perhaps also at the bulk chromatin level (Kalda et al, 2007). Furthermore, genetic studies have established a functional role for histone acetyltransferase (HAT) (Levine et al, 2005) and histone deacetylase (HDAC) activities in the mechanisms of action of psychostimulants, a view also supported by pharmacological experiments with HDAC inhibitors (HDACi) (Kalda et al, 2007;Kumar et al, 2005;Renthal et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A preclinical study has shown that multiple injections of VPA when delivered consecutively after methamphetamine could reduce the addictive behavior in rodents (Kalda et al. 2007). Consistently, clinical studies suggest that cocaine craving and abuse are diminished by treating cocaine abusers with valproate (Halikas et al.…”
Section: Discussionmentioning
confidence: 99%
“…Acute and chronic administration of psychostimulants and morphine elicits histone modifications such as histone acetylation at a specific subset of learningassociated genes in the brain reward circuitry including the VTA that could facilitate and consolidate lasting neural and behavioral plasticity induced by drug abuse. Moreover, increasing histone acetylation through pre-or coadministration of histone deacetylase (HDAC) inhibitors (HDACis) in conjunction with abused drugs promotes or opposes drug-induced synaptic and behavioral abnormalities, suggesting that this epigenetic mark might be required to potentiate or prevent an addicted state (Jing et al 2011;Kalda et al 2007; Kennedy et al 2013;Kumar et al 2005;Levine et al 2005;Renthal et al 2007Renthal et al , 2009Sanchis-Segura et al 2009;Sun et al 2012;Wang et al 2010). This opens the possibility of targeting epigenetic mechanisms during initial learning or memory retrieval of drug-associated cues as a novel pharmacological therapy for extinction of drug-seeking behaviors.…”
Section: Learning Mechanisms In Brain Reward Pathways Are Hijacked Afmentioning
confidence: 99%